Genome-wide identification and functional analysis of PEL gene family in Brassica napus L - Man Xing; Yu Kang; Mengjie Lv; Bheem Raj Serani; Qi Shen; Wenfang Jiao; Wen Mu; Shan Chen; Zechuan Peng; Luyao Huang (BMC Plant Biology)
Abstract Background The function of the PEL gene has recently been studied in rice and Arabidopsis. Overexpression of the PEL1 gene leads to the Pseudo-Etiolation in Light phenotype. PEL1 downregulates chlorophyll accumulation in Arabidopsis and rice, and knocking out genes that downregulate chlorophyll content may improve crop quality and yield. However, the role of the PEL gene family in Brassica crops has not yet been reported. Results This study identified 24 members of PEL gene family in Brassica napus (B. napus), Brassica rapa (B. rapa), Brassica oleracea (B. oleracea), and Arabidopsis thaliana. Among them, PEL1 and PEL3 encode acidic proteins, while PEL2 and PEL4 encode weakly basic proteins. Phylogenetic and collinearity analyses showed that PEL genes are highly conserved and share a common domain (A_thal_3526). We cloned the BnaPEL1 gene from B. napus, and overexpression resulted in yellowing leaves and reduced chlorophyll content. CRISPR/Cas9-mediated knockout of BnaPEL1 increased chlorophyll content, enhanced photosynthesis, and improved yield. Transcriptome analysis revealed that differential genes are involved in carbohydrate metabolism and translation, with key roles in nucleocytoplasmic transport and chlorophyll biosynthesis. Conclusions Our study concludes that BnaPEL1 negatively regulates chlorophyll content and its knockout enhances photosynthesis and yield in rapeseed. The present study lays the foundation for the functional research and application of the PEL gene in oilseed rape.